Poorly differentiated clusters: prognostic significance in colorectal carcinomas - Jurescu, Aura; Văduva, Adrian; Tăban, Sorina; Gheju, Adelina; Olteanu, Gh.; Mihai, Ioana; Lăzureanu, Codruța; Cornianu, Marioara; Lazăr, Fulger; Dema, Alis (Polish Journal of Pathology, 2019)
Colorectal cancer (CRC) remains a major public health burden worldwide, despite increased knowledge on its pathogenesis and advances in therapy. We aimed to evaluate a new histological grading system based on poorly differentiated clusters (PDCs) counting – the PDCs grade (PDCs-G), and its clinicopathological and prognostic significance, compared to the World Health Organisation (WHO) grading system (WHO grade). We reviewed 71 surgical resection specimens for CRC from the Emergency County Hospital “Pius Brînzeu” Timisoara. The cases were graded using the WHO grade and the PDCs-G, with further analysis of their association with the other recognised prognostic parameters. Using the WHO grade, 9% of the analysed cases were G1, 80% G2, 11% G3, and none of the tumours was graded G4, while in the PDCs-G 16% were G1, 45% G2, and 39% G3. In multivariate analysis PDCs-G was significantly associated with the American Joint Committee on Cancer stage of the disease (AJCC stage) (p = 0.0003), depth of invasion (pT) (p = 0.0084), nodal status (LNM) (p < 0.0001), lymphovascular invasion (LVI) (p < 0.0001), perineural invasion (PNI) (p < 0.0052), and tumour border configuration (p < 0.0001). The novel grading system based on PDCs counting is an additional histological tool in the evaluation of CRC and a promising new prognostic factor for these patients.